9x+29=93-5x

Simple and best practice solution for 9x+29=93-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+29=93-5x equation:


Simplifying
9x + 29 = 93 + -5x

Reorder the terms:
29 + 9x = 93 + -5x

Solving
29 + 9x = 93 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
29 + 9x + 5x = 93 + -5x + 5x

Combine like terms: 9x + 5x = 14x
29 + 14x = 93 + -5x + 5x

Combine like terms: -5x + 5x = 0
29 + 14x = 93 + 0
29 + 14x = 93

Add '-29' to each side of the equation.
29 + -29 + 14x = 93 + -29

Combine like terms: 29 + -29 = 0
0 + 14x = 93 + -29
14x = 93 + -29

Combine like terms: 93 + -29 = 64
14x = 64

Divide each side by '14'.
x = 4.571428571

Simplifying
x = 4.571428571

See similar equations:

| 10-(-10)-7-5=x | | 8.5x-3.5x=-94 | | (-11)-8+1-(-6)=x | | 4x+2=x-11 | | (-3)+5+(-5)+12=x | | x/2+3=1/2 | | 6+(-7)+(-5)-(-2)=x | | 6y=45-3y | | 7+(-1)+12-7=x | | (-11)-(-14)+7=x | | 9+6(2)7n= | | 0.5x-1.4=1.1 | | (-7)-(-2)-9=x | | -6-1=-32y+32 | | 16-(-13)-(-5)=x | | 6(y-4)=5[17-3(2y-13)] | | 4-5+7k=33 | | -9-200x+(0.015)(100)= | | (-16)-6+(-5)=x | | 12+0.4(x-2)=10 | | 6(x+2)+4=-6 | | 52x=104 | | 8y-5=6y+7 | | -33m-14=85 | | 5x+5x+3+8=5x+4+4x | | -r+259=-124 | | -2x^2+12x+3=0 | | 3(3+2r)=5-6(r+2) | | 3(2x-4)=5(x+6) | | 7x-6-4x=4x-3 | | 2.1x+1=7 | | 9x-3x=-26+2 |

Equations solver categories